Molecular Bacteriology: Protocols and Clinical Applications - Woodford, Neil.; Woodford, Neil.; Johnson, Alan.; Johnson, Alan. (Methods in Molecular Medicine,, 1998)
In Molecular Bacteriology: Protocols and Clinical Applications, Woodford and Johnson bring together in a single volume a state-of-the-art collection of detailed molecular methods for the diagnosis and clinical investigation of bacterial infections. These wide ranging techniques-each presented by recognized experts who have fine-tuned their methods for optimum performance-will permit readers to establish them successfully in their own laboratories. An accompanying series of minireviews highlights and explains the clinical and epidemiological relevance of the techniques and shows how they may be applied to major pathogen species and various types of antibiotic resistance. Molecular Bacteriology: Protocols and Clinical Applications enlarges our current understanding of the role that molecular methodology can play in modern medical bacteriology, fully explaining both the practical and theoretical aspects of the cutting-edge methods that are increasingly finding diagnostic use in laboratories throughout the world. An authoritative laboratory resource for everyone working with infectious diseases today, this book's insightful reviews and detailed protocols will soon win many devotees.